Morphometry of the ribeirão dos pinheirinhos watershed, brotas?SP - Silva, Jéssika Luane; Tonello, Kelly Cristina (IRRIGA, 2014)
The objective of this study was to perform morphometric analyses of the Ribeirão dos Pinheirinhos watershed, Brotas, SP which could contribute to improve management of natural resources and environmental planning. With this in mind, morphometric parameters were defined based on cartographic data and data plans, using the GIS software IDRISI Andes version. The drainage area is 92.57 km2 and the watershed has an elongated shape as a result of low Compactness Coefficient (Kc) away from 1 (one) (1.647), Form Factor (0.622) and Index of Roundness (CI) (0.363). Such indices show a little circular shaped watershed, which leads to longer time of rain water concentration and lower risk of flood. The drainage density was 2.717 km/km-2 showing good drainage, which was confirmed by the dendritic pattern and fourth- order branching grade. The refief is considered flat to undulating, 520 m minimum and 834m maximum altitude. Morphometric characterization is an important tool for understanding physical conditions and interactions in the hydrographic watershed. It provides subsidies for diagnosis, management and environmental planning for conservation and appropriate management, and therefore sustainable use of natural resources.
Morfometria da bacia hidrográfica do ribeirão dos pinheirinhos, brotas-SP
Keywords: Drainage; Environmental Planning; Gis; Hydrology; Morphometry; Resource Management; Water Planning; Water Resources; Watershed; Pinheiros River; Sao Paulo [brazil]